1998
DOI: 10.1016/s0736-5748(98)00025-2
|View full text |Cite
|
Sign up to set email alerts
|

Do early‐life events permanently alter behavioral and hormonal responses to stressors?

Abstract: Early-life stimulation (e.g., brief handling) attenuates the behavioral and neuroendocrine responses to stressors encountered in adulthood, particularly with respect to activation of hypothalamic-pituitary-adrenal (HPA) activity. In contrast, if neonates were subjected to a more severe stressor, such as protracted separation from the dam or exposure to an endotoxin, then the adult response to a stressor was exaggerated. These early-life experiences program HPA functioning, including negative feedback derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
332
1
9

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 581 publications
(371 citation statements)
references
References 67 publications
25
332
1
9
Order By: Relevance
“…Environmental enrichment during the perinatal period has been shown to have either positive or detrimental developmental or behavioural effects (Mychasiuk et al 2012;Zhu et al 2006;Mann and Gervais 2011;Anisman et al 1998) and various variables could account for discrepancies between enrichment studies. For example, variability in maternal behaviour could depend on rat strain, in particular as rat strains differ in anxiety-related behaviour (Rosenfeld and Weller 2012;Rex et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental enrichment during the perinatal period has been shown to have either positive or detrimental developmental or behavioural effects (Mychasiuk et al 2012;Zhu et al 2006;Mann and Gervais 2011;Anisman et al 1998) and various variables could account for discrepancies between enrichment studies. For example, variability in maternal behaviour could depend on rat strain, in particular as rat strains differ in anxiety-related behaviour (Rosenfeld and Weller 2012;Rex et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is not surprising that sensory deprivation during this period has detrimental and long-lasting, if not permanent, effects on the nervous system and a variety of behaviours. Stressful experiences during the early postnatal period can programme an anxious phenotype (Anisman et al 1998). It has been suggested that exposure to adverse environmental factors during the maturation of brain anxiety circuits contributes to the pathogenesis of anxiety disorders (Leonardo and Hen 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In laboratory rodents, differences among strains have been observed in basal glucocorticoid levels as well as in stress-induced responses (e.g. Sakaguchi et al, 1984;Anisman et al, 1998). Birds commonly show population differences in response to stressors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…1991), but can also be influenced by experiences during ontogeny (Anisman et al. 1998) and the presence of social support (de Waal & van Roosmalen 1979; Heinrichs et al. 2003; Kanitz et al.…”
Section: Introductionmentioning
confidence: 99%